2013
DOI: 10.5897/ajb2013.12172
|View full text |Cite
|
Sign up to set email alerts
|

Study of seasonal sexual activity variations in Algerian rams: Sexual behaviour, testosterone concentration control and environmental factors

Abstract: This study focuses on the determination of seasonal effect on two main andrological sexual activity parameters within young and adults rams of Rembi breed from Algeria for a period of one year. The experiment involved a weekly evaluation of males' sexual behaviour and a monthly measurement of serum testosterone concentration in order to know the main testicular endocrine activity. The purpose of this experiment was to assess better the characteristics of the reproductive activity between two categories of rams… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 9 publications
0
7
0
3
Order By: Relevance
“…Our results seem to be in agreement with those of Benia et al . [ 34 ] who found that testosterone concentrations are maximal during spring and autumn months, and that OD rams showed continuous spermatogenetic activity during all seasons. In addition, serum testosterone levels were low during July where the temperature was very high on the day of collection.…”
Section: Discussionmentioning
confidence: 99%
“…Our results seem to be in agreement with those of Benia et al . [ 34 ] who found that testosterone concentrations are maximal during spring and autumn months, and that OD rams showed continuous spermatogenetic activity during all seasons. In addition, serum testosterone levels were low during July where the temperature was very high on the day of collection.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the time to achieve the first ejaculation was shorter. Seasonal variation in ejaculate latency occurs in Algerian rams (Benia et al., ), and Rekik et al. () reported that melatonin treatment increased total activity time and number of lateral approaches in a sexual behaviour test.…”
Section: Discussionmentioning
confidence: 99%
“…Hallap, Jaakma 19 reported a high percentage of spermatozoa with standard head and tail morphology in Estonian Holstein bulls. In general, scrotal circumference, as the most accessible measure of a bull's ability to produce adequate spermatozoa, correlates positively with testicular volume and semen quality 20 and negatively with the occurrence of spermatozoa defects 21 .…”
Section: Discussionmentioning
confidence: 99%